Das Londoner Schuldenabkommen: Die Regelung der deutschen Auslandsschulden nach dem Zweiten Weltkrieg - Ursula Rombeck-Jaschinski (Oldenbourg Verlag, 2005)
Das am 27. Februar 1953 unterzeichnete Londoner Schuldenabkommen stellte ein Novum in der Geschichte der internationalen Schuldenregelung dar. Mit ihm wurde die gigantische deutsche Auslandsverschuldung des privaten und öffentlichen Sektors aus der Vor- und Nachkriegszeit geregelt. Als Rechtsnachfolgerin des Deutschen Reiches übernahm die Bundesrepublik die Haftung für die gesamten Vorkriegsschulden des ehemaligen Reichs. Die langwierigen und von zahlreichen Schwierigkeiten durchzogenen Verhandlungen erreichten, dass das Schuldenabkommen dem tatsächlichen Leistungsvermögen der Bundesrepublik angepasst wurde. Mit dem Londoner Schuldenabkommen wurde die Kreditwürdigkeit der jungen Bundesrepublik wiederhergestellt; es war damit eine Conditio sine qua non für die Wiedergewinnung der Souveränität der Bundesrepublik Deutschland. – – The London debt-settlement agreement of 1953 resolved the questions of Germany's enormous foreign public and private-sector debts from the time before and after the war. The three Western Allies insisted on re-establishing the Federal Republic's credit-worthiness as a precondition for re-attaining sovereignty. During the war the British and Americans were already considering the question of Germany's debts, with the British taking the leading role. During the war and shortly thereafter the main issue was to secure legally the demands of foreign creditors against the competing claims for reparations. Once the East-West conflict started, the question of reparations became noticeably less prominent. Allied post-war supplies, and above all the Marshall Plan, then created further debts, which had to be dealt with first. Debt-reduction was unavoidable here if a general agreement on Germany's foreign debts was to be reached. The Americans played a key role, being the main creditors in almost all debt categories, and they made relentless use of this, much to the regret of the financially-weakened British. As far as Washington was concerned Germany's foreign debts were a means to an end in the context of American global strategy.
Keywords: 330; Internationale Staatsschulden; Schuldenerlass; Schuldenübernahme; Internationales Abkommen; Zeitgeschichte; Deutschland